2007
DOI: 10.1099/vir.0.83321-0
|View full text |Cite
|
Sign up to set email alerts
|

Norovirus recombination

Abstract: RNA recombination is a significant driving force in viral evolution. Increased awareness of recombination within the genus Norovirus of the family Calicivirus has led to a rise in the identification of norovirus (NoV) recombinants and they are now reported at high frequency. Currently, there is no classification system for recombinant NoVs and a widely accepted recombinant genotyping system is still needed. Consequently, there is duplication in reporting of novel recombinants. This has led to difficulties in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
278
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 296 publications
(297 citation statements)
references
References 61 publications
18
278
0
1
Order By: Relevance
“…By Simplot analysis, the cross over site was mapped upstream the conserved ORF1b/ ORF2 junction region. The exchange of genome fragments via recombination is common in single-stranded RNA viruses and appears to occur at higher frequency in highly conserved genomic regions among genetically related strains (Bull et al, 2007). Molecular recombination of genomic RNA can affect phylogenetic groupings, increase the virulence of the virus, confuse molecular epidemiological studies and have major implications in vaccine design (Bull et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By Simplot analysis, the cross over site was mapped upstream the conserved ORF1b/ ORF2 junction region. The exchange of genome fragments via recombination is common in single-stranded RNA viruses and appears to occur at higher frequency in highly conserved genomic regions among genetically related strains (Bull et al, 2007). Molecular recombination of genomic RNA can affect phylogenetic groupings, increase the virulence of the virus, confuse molecular epidemiological studies and have major implications in vaccine design (Bull et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The exchange of genome fragments via recombination is common in single-stranded RNA viruses and appears to occur at higher frequency in highly conserved genomic regions among genetically related strains (Bull et al, 2007). Molecular recombination of genomic RNA can affect phylogenetic groupings, increase the virulence of the virus, confuse molecular epidemiological studies and have major implications in vaccine design (Bull et al, 2007). As seen in noroviruses, the highly conserved junction region connecting the non-structural and structural genes of HAstVs seems to be a recombination hot spot (De Grazia et al, 2012;Wolfaardt et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…While Lindesmith and coworkers have identified a recombination breakpoint at residue 265 located near the P1-1/P2 domain interface of NoV GII.4 strains (Lindesmith et al, 2008), this recombination break point was not found in this study. The absence of detected recombinants might be due to the fact that we did not have access to ORF1/ORF2 overlap sequences, previously found associated with NoV recombination break points (Bull et al, 2005(Bull et al, , 2007Phan et al, 2007). Thus, we cannot rule out that recombination occurred at the ORF1/ORF2 junction.…”
mentioning
confidence: 96%
“…Since RNA recombination is believed to be one of the major driving forces in viral evolution (Worobey & Holmes, 1999), including NoV (Bull et al, 2005(Bull et al, , 2007Phan et al, 2007), we searched the 134 full-length (P1-1 and P2 capsid domains) NoV capsid nudeotide sequences for recombination events. The sequences were first aligned using CLUSTAL W-multialign with default settings on the Mobyle portal (Pasteur Institute), and then analysed by the RDP2 software to search for possible recombinants using different conventional recombination detection methods such as GENECONV, SIMPLOT, BOOTSCAN, MAXIMUM x 2 and CHIMAERA (Martin et al, 2005).…”
Section: No Recombination Detected Within the P1-1 And P2 Capsid Domainsmentioning
confidence: 99%
See 1 more Smart Citation